Ketahanan Kadar Vitamin C dan Kadar Air Pada Cabai Merah Besar (Capsicum Annuuml) dengan Berbagai Jenis Kemasan - Heny M. C. Sine (Politeknik Pertanian Negeri Kupang, 2013)
Resistance levels of vitamin cand water content on a large red chillies (capsicum annuuml.) With different types of packaging The aim of this study is to obtain a type of packaging that can preserve high levels of vitamin C and low moisture loss. This research used Completely Randomized Design (CRD), consisting of four packaging treatments which are A. Poliethylen plastic; B. gunny; C. Palm leaf material; D. without packaging. Each treatment was repeated five times with total of twenty trials. There was an effect on water content and the levels of vitamin C. Poliethylen plastic packaging is not significantly different with palm leaf material packaging in loss of low water levels and a high content of vitamin C levels obtained. Low vitamin C and low water content was obtained on treatment with gunny packaging and without packaging.Key words: Vitamin C, packaging, Capsicun annum L